FEATURES OF CUMULATIVE CONSOLIDATION AND FRACTAL DIMENSION OF POWDER MATERIALS SURFACE OF AL-CU SYSTEM ON THE GRANULATED ALUMINIUM BASIS - A. Y. KEM; L.A. ARESTOVA (Advanced Engineering Research)
The dependence of pressings density on the basis of the granulated aluminium powder is investigated. The definition technique of fractal dimension of powder materials surface is offered.